PENGARUH NILAI KECUKUPAN MODAL DAN BATAS MAKSIMUM PEMBERIAN KREDIT TERHADAP TINGKAT LIKUIDITAS BANK PADA BANK JABAR BANTEN - M. Taufik Aziz; Fitri Rayanti (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2017)
Bank Indonesianing to constitute central bank that give minimum capital rule that shall be of service on bank. Measure that utilized by Indonesia Bank in determine minimum capital is capital sufficiency ratio or Capital Adequacy Ratio (CAR). Impact of regulation hits CAR that is limitation who shall be noticed by bank in order to do its effort development. If limitation CAR is not is shown, jeopardy who may happen is decreased level CAR bank that on eventually will get implication to healths level decrease bank. By use of data of Jabar Banten's bank year 2011 2015, this research intent to see CAR'S influence (X1) and Application Maximum Bounds Credit (BMPK) as X2 to increase bank liquidity (Loan to is Ratio's Deposit or LDR) as Y. CAR Jabar Banten's Bank, since March 2011 until with March period 2015 continually experiences decrease. Presentase averagely supreme BMPK happening on year 2011, which is as big as 0.20%, meanwhile presentase is happening lowest on year 2012. CAR'S affecting relationship and BMPK to LDR on Jabar Banten's Bank points out that affecting subjective happening signifikan's one. It because of have probability point as big as 0.041> 0. 05. Therefore, assess determinant coefficient just as big as 0.24 or 24% its means represented capital structure variable by CAR (X1) and BMPK (X2) having influence to LDR firm as big as 24% and its rest as big as 76% regarded by other factors. Key Words : Capital Adequacy Ratio, Application Maximum Bounds Credit and Liquidity.